2019
DOI: 10.1111/apt.15331
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term metformin use may improve clinical outcomes in diabetic patients with non‐alcoholic steatohepatitis and bridging fibrosis or compensated cirrhosis

Abstract: Summary Background Metformin may protect against hepatocellular carcinoma and mortality among patients with type 2 diabetes. Aim To investigate whether long‐term use of metformin improves survival and reduces liver‐related outcomes among patients with type 2 diabetes and non‐alcoholic steatohepatitis. Methods A total of 191 diabetic patients with biopsy‐proven non‐alcoholic steatohepatitis and bridging fibrosis or compensated cirrhosis were retrospectively identified at Indiana University Medical Center betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 43 publications
(97 reference statements)
1
39
2
6
Order By: Relevance
“…We thank Dogru et al for their insightful comments on our recent article. 1,2 We demonstrated that long term and continued use of metformin lowers risk of death or transplant and hepatocellular carcinoma (HCC) in type 2 diabetic patients with non-alcoholic steatohepatitis (NASH) and advanced fibrosis. Dogru et al suggested that benefits of metformin intake on adverse clinical outcomes might be mediated by improving insulin sensitivity and perhaps regulating insulin-like growth factor/ insulin axis.…”
Section: Editorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Dogru et al for their insightful comments on our recent article. 1,2 We demonstrated that long term and continued use of metformin lowers risk of death or transplant and hepatocellular carcinoma (HCC) in type 2 diabetic patients with non-alcoholic steatohepatitis (NASH) and advanced fibrosis. Dogru et al suggested that benefits of metformin intake on adverse clinical outcomes might be mediated by improving insulin sensitivity and perhaps regulating insulin-like growth factor/ insulin axis.…”
Section: Editorsmentioning
confidence: 99%
“…Eight studies involving 134 202 metformin users and 60 352 non-users were included (Table 1). 1,2,[4][5][6][7][8][9] The mean follow-up ranged from 2.8 to 6.8 years. The incidence rate of HCC ranged from 0.03% to 7.69% among metformin users, and 0.046% to 50% among nonusers.…”
Section: Ack N Owled G Em Entsmentioning
confidence: 99%
“…EDITORS, Vilar-Gomez et al found that the long-term use of metformin is positively associated with a decrease in the risk of overall mortality, the need for liver transplantation and the development of hepatocellular carcinoma (HCC) in diabetic patients with non-alcoholic steatohepatitis (NASH) and bridging fibrosis or compensated cirrhosis. 1 The authors hypothesize several pathways that potentially define the beneficial effects of metformin, including decrease in insulin-like growth factor-1, activation of AMP-activated protein kinase, inhibition of mammalian target rapamycin, downregulation of human epidermal growth factor receptor-2, reduction in endogenous production of reactive oxygen species and associated DNA damage, and others. [2][3][4][5] Increasing evidence suggests that intestinal dysbiosis plays a key role in the development and progression of metabolic liver disorder.…”
Section: Letter: Improvement Of Clinical Outcomes By Metformin In Metmentioning
confidence: 99%
“…2 Therefore, the incidence rate of HCC was 6.36% (7/110) and 25.93% (21/81) among diabetic patients with or without long-term metformin treatment. 1 This raises a question about the intensity of surveillance for HCC in such patients. Current HCC surveillance guidelines propose biannual liver ultrasound for patients with cirrhosis.…”
Section: Letter: Metformin Reduces the Risk Of Hepatocellular Carcinomentioning
confidence: 99%
“…Eight studies involving 134 202 metformin users and 60 352 non-users were included (Table 1). 1,2,[4][5][6][7][8][9] The mean follow-up ranged from 2.8 to 6.8 years. The incidence rate of HCC ranged from 0.03% to 7.69% among metformin users, and 0.046% to 50% among nonusers.…”
Section: Letter: Metformin Reduces the Risk Of Hepatocellular Carcinomentioning
confidence: 99%